Removal of excess nutrients by Australian zeolite during anaerobic digestion of swine manure. Issue 4 (21st March 2018) - Wijesinghe, D. Thushari N.; Dassanayake, Kithsiri B.; Scales, Peter; Sommer, Sven G.; Chen, Deli
ABSTRACT: The objective of this study was to investigate the feasibility of using natural and NaCl-treated Australian zeolites to simultaneously remove excess nutrients from anaerobically digested swine manure. Ion adsorption and desorption properties of Australian zeolite during the anaerobic digestion of swine manure were investigated. Two experiments were conducted: the first was an adsorption experiment with multi-component solutions that corresponded with the ionic composition of swine manure digestates. The second experiment determined the effects of zeolite dose rates during anaerobic digestion of swine manure on the removal of N, P and K from solution. Adsorption isotherms confirmed selectivity for K + over NH4 + by Australian natural and sodium zeolites. Therefore, NH4 + removal was considerably reduced when there was simultaneous K + uptake. Natural zeolite desorbed more Ca 2+ during K + and NH4 + adsorption than sodium zeolite. The ion exchange reaction was independent of the presence of P. P removal was very dependent on the pH of the medium. Natural Australian zeolite was shown to be a potential sorbent for the removal of NH4 +, K + and P during the anaerobic digestion of swine manure. However, the application of high concentrations of zeolite at higher pH values (> 7.5) might not be appropriate for anaerobic digestion, because zeolite desorbed more Ca 2+ ions into the solution at the higher doses of zeolite and then availability of P for microbial growth might be reduced as a result of PO4 3− precipitation with Ca 2+ at the higher pH.